Суспільно-політичні взаємини між національними силами Східної Галичини та Наддніпрянщини в 1917–1918 рр. - Скорич, Л. В. (Видавництво Національного університету "Львівська політехніка", 2009)
The describes basic facts which determined public-political mutual relation between Ukrainians people of East Galichina and Dnipro region.
Keywords: nation revolution; Ukrainian People Republic; Sichovi Striltsi